Evaluación de luminosidad en alumbrado público con luminarias led. - Alava Quimis, Marlon Andrés (2019)
In this research work, an evaluation of public lighting was carried out with led luminaires in La Merced, Ambato. Due to the fact that it circulates through the sector during the night, irregular levels of luminosity are perceived, as well as apparent excesses of light. For that, a field evaluation is carried out involving the division of the sector by floods and a measurement of luminosity levels by measuring equipment (luxometer). In addition, a requalification of the sector was developed based on the regulation of luminosity of avenues according to vehicular and pedestrian traffic density at night; arranged by regulations on public lighting. Agency for Regulation and Control of Electricity (ARCONEL) adopts the parameters of international normative: Illumination Engineering Society of North America (IESNA). In order to determine if existing public lighting parameters are within the normative and if it isn’t, an improvement proposal that allows modifying certain parameters (level of luminosity and glare caused, installation height, separation distance, distribution of the luminaries, uniformity of the avenues, and others) is run. After carrying out an analysis between measured values and values obtained through the improvement proposal (executed in DiaLUX software), it is verified with a correct evaluation and installation of public lighting in the sector. Luminous excesses can be reduced up to 45.12% in critical points of illumination (placed under the lamp). In addition, uniformity improves from 0.36 to 0.37. This level of uniformity is closer to the value indicated by ARCONEL.